Multiwalled carbon nanotube-poly vinyl alcohol nanocomposite multifunctional coatings on aerospace alloys. (2018) - Verma, Parul; Anoop, S.; Sasidhara Rao, V.; Sharma, A.K.; Uma Rani, R.; Antony, P.J.
Abstract: Multiwalled carbon nanotube (MWCNT)-polymer composites proved to be multifunctional materials with improved chemical resistance, thermal conductivity, electrical conductivity, etc. In the present work nanocomposite coating of multiwalled CNTs dispersed in poly vinyl alcohol (PVA) was prepared on anodized alloys viz., AA 6061, Mg AZ31B and pretreated Ti6Al4V. Aqueous solution of 0.5% MWCNTs dispersed in PVA was coated using dip coating technique. Heat treatment of the coatings was carried out at 200 °C for two hours. Infrared emissivity and solar absorptivity of coating were measured. Coating adhesion was tested based on cross hatch tape test. Surface morphology was studied by using Field Emission Scanning Electron Microscopy and chemical composition was obtained by Energy-dispersive X-ray spectroscopy. Solar absorbance (αs ) and IR emittance (εIR ) was found as 0.94 and 0.90 respectively. MWCNT-PVA coatings proved to be a good alternative for spacecraft passive thermal control coatings